Factors influencing the development of digital human resources in digital transformation in Vinh Phuc province - Vu Xuan Nam; Nguyen Hoang Nguyen (Journal of State Management, 2024)
This article applies a multivariate regression method to evaluate factors affecting digital human resources in digital transformation activities, using data collected from enterprises, organizations, and individuals in Vinh Phuc province. The study reveals that enhancing human resource capabilities through training and skill development significantly improves the efficiency of digital transformation in Vinh Phuc. The research findings provide a theoretical basis and propose solutions for managers and policymakers to strengthen digital human resources and accelerate the Province's digital transformation in the current context.